Security in Emerging Wireless Communication and Networking Systems First International ICST Workshop, SEWCN 2009, Athens, Greece, September 14, 2009, Revised Selected Papers - Gu, Qijun; Zang, Wanyu; Yu, Meng.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the First International ICST Workshop, SEWCN 2009, held in Athens, Greece, in September 2009. The workshop emphasizes on new ideas for secure architectures and protocols to enhance the emerging wireless systems. The 7 selected full papers cover topics on applied cryptography, key management, vulnerability analysis, privacy, authentication, and intrusion detection for emerging wireless systems. .
Session 1 - Session Chair: Nikolaos Preve -- A Closed-Form Expression for Outage Secrecy Capacity in Wireless Information-Theoretic Security -- Enhanced Access Polynomial Based Self-healing Key Distribution -- Security Flaws in an Efficient Pseudo-Random Number Generator for Low-Power Environments -- Session 2 - Session Chair: Theofilos Chrysikos -- RSSI-Based User Centric Anonymization for Location Privacy in Vehicular Networks -- Integrating Wireless Sensor Networks with Computational Grids -- Security for Heterogeneous and Ubiquitous Environments Consisting of Resource-Limited Devices: An Approach to Authorization Using Kerberos -- Signalprint-Based Intrusion Detection in Wireless Networks.
Keywords: Computer science; Computer organization; Computer communication systems; Computer security; Data structures (Computer science).; Data encryption (Computer science).; Coding theory; Computer Science; Computer Communication Networks; Coding and Information Theory; Data Encryption; Systems and Data Security; Data Structures, Cryptology and Information Theory; Computer Systems Organization and Communication Networks; Electronic books